Gelation of soybean proteins induced by sequential high-pressure and thermal treatments - Speroni Aguirre, Francisco José (2009)
The effect of high-pressure treatment on structural and rheological properties of soybean protein dispersions was studied. A sequential high-pressure/thermal treatment was also analyzed. Dissimilar effects on soy protein isolate (SPI) and the enriched soybean protein fractions: b-conglycinin (bCEF) and glycinin (GEF) were observed. High pressure (600 MPa) promoted bCEF gelation, but did not modify the rheological properties of GEF in spite of its complete denaturation. Pressure treatment also induced the establishment of hydrophobic interactions and disulfide bonds that allowed the formation of soluble high molecular mass aggregates from the different polypeptides of both b-conglycinin and glycinin. Protein strands formation was detected in matrix microstructure of HP-treated SPI and bCEF dispersions in accordance with their rheological behavior of weak gels. In the case of GEF modifications induced by HP in the microstructure (apparition of large granules) were not accompanied by rheological changes. Heating process after HP treatment induced protein gelation. A decrease in the temperature of onset of matrix formation of SPI and bCEF samples was observed. The magnitude of this effect was proportional to the intensity of HP treatment. Contrarily, HP provoked a delay in gelation process of GEF dispersions. During the thermal cycle, previous HP treatment diminished the ability of both soybean globulins to establish hydrophobic interactions on heating and hydrogen bonds on cooling, thus obtaining gels with small elastic modulus.